Influence of Friction Pressure at a Given Burn-off Length on the Mechanical and Microstructural Properties of Welded Joints from Medium-Carbon Alloyed Steels in Rotaty Friction Welding - Priymak, Elena; Firsova, Nadezhda; Bashirova, Elena; Sergienko, Svetlana; Kuzmina, Elena; Atamashkin, Artem (International Journal of Engineering and Technology, 2018)
This study investigates the inï¬‚uence of friction pressure at a givenÂ burn-off length on the microhardness, tensile properties and microstructure of the welded joints from steel 32-2-Mn and 40-Cr-Ni. Phase transformations occurring in the materials to be welded as a result of thermal deformation effects are analyzed. The change in the length of the thermomechanical affected zone (TMAZ) depending on the friction pressure is shown. The results of the distribution of microhardness in the weld, clearly illustrating the formation of hardened and weakened areas. The results of tensile tests of welded joints are given. Analyzed the place of fracture at various welding parameters. The necessity of studying the distribution of internal residual stresses to explain the mechanism of fracture of welded joints is shown.Â Â